Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/coa.12382
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between lipoprotein ratios and hearing outcome in idiopathic sudden sensorineural hearing loss patients

Abstract: We suggested that lipoprotein ratio of LDL-C/HDL-C may be a prognostic factor for hearing recovery in ISSNHL patients. Further studies should be conducted to determine whether hearing outcomes in ISSNHL can be improved by changing patients' lipid profiles via antilipidemic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“… 17 The negative prognostic value of total cholesterol concentrations and of high LDL/HDL ratio have already been reported. 6 , 7 , 20 Lin et al . 21 provided evidence that comorbid diabetes or hypercholesterolemia may indicate a smaller probability of improvement for patients with SSHL, moreover a recent work by Jung et al .…”
Section: Discussionmentioning
confidence: 99%
“… 17 The negative prognostic value of total cholesterol concentrations and of high LDL/HDL ratio have already been reported. 6 , 7 , 20 Lin et al . 21 provided evidence that comorbid diabetes or hypercholesterolemia may indicate a smaller probability of improvement for patients with SSHL, moreover a recent work by Jung et al .…”
Section: Discussionmentioning
confidence: 99%
“…2,15,26,27 Most researchers believed that a higher initial hearing threshold was an indicator of a poor prognosis in SSNHL patient, 2,15,26 but some studies failed to observe an association between initial hearing threshold and hearing improvement. 28 Moreover, Lin et al 21 said that comparisons between those reports must be treated with caution because of different recovery evaluation criteria. In our study, our results showed higher initial hearing threshold was significantly correlated with a poor prognosis by both Siegel's criteria and CMAO criteria which was in accord with most previous reports.…”
Section: Effect Of the Initial Hearing Threshold On Hearing Recoverymentioning
confidence: 99%
“…Hyperlipemia is one of the risk factors of cardiovascular disease, which increases blood viscosity and alters vasomotion (9). Recent reports have identified hypercholesterolaemia as a significant risk factor for ISSNHL (10,11). A systematic review and meta-analysis of the relationship between serum lipids and ISSNHL did not provide evidence for the association between them, nor did it definitively rule out such an association (12).…”
Section: Introductionmentioning
confidence: 98%